REKONSTRUKSI SISTEM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Burhanuddin, Hamam (MUADDIB Jurnal Kependidikan dan Keislaman, 2014)
Learning is a complex activity in education, good teaching needs to be supported by systems and components, some of the learning system are students, teachers, methods (strategies) learning, learning activities and evaluation tool selection, some of these components are interrelated each other and support each other, to achieve the goal of education is needed in schools PAI (Islamic Education) assessment, some of the components of the learning objectives can be achieved as expected. Thus, reconstruction some of components is expected to maximize the learning activities at school, so the PAI learning objectives can be achieved.